Implementation of the Fun Model in Increasing Learning Concentration in Early Childhood at the Taman Fioretty Orphanage - Rendo, Elisabeth F.C.; Mutmainah, Destiani; Afifa, Fika Nur; Awalia, Maulida; Prasetya, Nabilla Aprilia; Riandri, Nimas Febriana; Watini, Sri (Lembaga Penelitian dan Pendidikan Mandala, 2024)
Concentration on children's learning at an early age is an important aspect in the learning process. The ASYIK Play Model is an abbreviation of Safe, Happy, Confident, Confident, Innovative and Creative. The ASYIK model is a model that can be used to increase children's learning concentration at an early age. This research aims to increase learning concentration in children by using the ASYIK Play Model as well as rewards and shouts for early childhood at the Taman Fioretty Orphanage, Kampung Sawah, Bekasi, West Java. Apart from that, what the researchers want to achieve is to be able to motivate children to be able to carry out activities independently and enthusiastically. The research method used is qualitative description which is focused on the basis of facts carried out by observation, interviews and studying documents. The research results show that the ASYIK Play Model can help improve children's learning concentration.